In silico characterisation of the avocado WAK/WAKL gene family with a focus on genes involved in defence against Phytophthora cinnamomi - Harvey, Aaron; van den Berg, Noëlani; Swart, Velushka (Frontiers in Plant Science, 2025)
The avocado industry faces a significant threat from the hemibiotrophic oomycete pathogen Phytophthora cinnamomi. A variably expressed defence gene during an avocado infection trial was a Wall-associated kinase (WAK). WAK and WAK-Like (WAKL) proteins are known to bind to fragmented pectin (oligogalacturonides) produced during pathogen penetration, thereby activating downstream defence-related pathways. To better understand the P. cinnamomi-avocado defence interaction, this gene family was assessed using in silico methods. In this study, previously generated RNA-sequencing data were used to associate genes with the defence response, followed by promoter- and phylogenetic analysis of these genes/proteins. The predicted proteins from these genes were modelled with AlphaFold2, and structural similarity across different rootstocks, as well as their binding affinity for oligogalacturonides, were assessed. The analysis identified 14 Persea americana (Pa)WAKs and 62 PaWAKLs across the West-Indian (pure accession reference), Dusa®, Leola™ and R0.12 avocado rootstock genomes. These genes showed distribution across the West-Indian genome’s chromosomes, with MCScanX analyses predicting tandem duplications. PaWAK/WAKL expression profiles were compared, implicating five PaWAK/WAKLs in defence. Phylogenetic and promoter analyses were conducted to predict associated defence-related pathways, focusing on stress and phytohormone-responsive pathways. Structural differences and varying oligogalacturonide binding affinities of PaWAK/WAKLs were predicted across rootstocks. These defence-related genes could be incorporated into a molecular screening tool to improve the development of resistant avocado rootstocks.